Pelvic Floor Muscle Strength Stress Urinary Incontinence: Kekuatan Otot Dasar Panggul dan Stres Inkontinensia Urin - Asih Anggraeni; Surahman Hakim; Budi I. Santoso; Tyas Priyatini; Fernandi Moegni (Indonesian Socety of Obstetrics and Gynecology, 2020)
Objective: To examine the relationship between muscle strength and muscle thickness of levator ani with stress urinary incontinence (SUI) in women.Methods: This study uses a comparative cross-sectional study design. We collected 82 women who visiting the Obstetrics and Gynecology clinic of RSUPN Dr. Cipto Mangunkusumo with the study group were subjects with positive cough tests while the control group were subjects with negative cough tests. The data obtained in the form of history taking, Questionnaire for Urinary Incontinence Diagnosis (QUID), physical examination (POPQ), cough test. perineometer, and ultrasound.Results: We found no significant difference between the levator ani muscle thickness to the incidence of SUI with the median levator ani muscle thickness 0.63 cm (range 0.31-1.02 and p = 0.897). While levator ani muscle strength against SUI has a median of 19.5 (range 4.6-88.6 and p = 0.001). In multivariate analysis it was found that purely SUI, prolapse and age had no significant effect on the strength of levator ani muscles with a p-value of 0.243; 0.844; 0.903.Conclusions: There is no significant difference in levator ani muscle thickness between women who experience SUI compared to those who do not. Women with SUI have weaker levator ani muscle strength than those who do not experience but are not statistically significant. And there is no correlation between muscle strength and levator ani muscle thickness in women with SUI.Keywords: muscle strength, muscle thickness, perineometer, stress urinary incontinence, ultrasound. Abstrak Tujuan : Untuk mengkaji hubungan antara kekuatan otot dan ketebalan otot levator ani dengan keluhan IU-T pada perempuan.Metode : Penelitian ini menggunakan desain perbandingan potong lintang dengan melibatkan 82 wanita yang berkunjung di poliklinik Obstetri dan Ginekologi RSUPN Dr. Cipto Mangunkusumo dengan kelompok studi adalah subyek dengan tes batuk positif sedangkan kelompok kontrol adalah subyek dengan tes batuk negative. Data yang diperoleh berupa hasil anamnesis, Questionnaire for Urinary Incontinence Diagnosis (QUID), pemeriksaan fisik (POPQ), tes batuk. perineometer , dan USG.Hasil: Hasil penelitian ini didapatkan tidak ada perbedaan bermakna antara ketebalan otot levator ani terhadap kejadian IUT dengan median ketebalan otot levator ani 0,63 cm (jarak 0,31-1,02 dan p=0,897). Sedangkan kekuatan otot levator ani terhadap IUT memiliki median 19,5 (jarak 4,6-88,6 dan p=0,001). Pada analisis multivariat didapatkan bukti bahwa secara murni IUT, prolap dan usia tidak mempunyai pengaruh bermakna terhadap kekuatan otot levator ani dengan nilai p masing-masing 0,243; 0,844; 0,903.Kesimpulan : Tidak terdapat perbedaan yang bermakna pada ketebalan otot levator ani antara perempuan yang mengalami IU-T dibanding yang tidak mengalami. Perempuan IU-T mempunyai kekuatan otot levator ani yang lebih lemah dibanding yang tidak mengalami, namun tidak bermakna secara statistik. Tidak terdapat hubungan korelasi antara kekuatan otot dan ketebalan otot levator ani pada perempuan yang mengalami IU-T. Kata kunci : inkontinensia urin jenis tekanan, ketebalan otot, kekuatan otot, perineometer, USG